Understanding motivations for large US cannabis firms' participation in the cannabis space: Qualitative study exploring views of key decision‐makers. (13th February 2020) - Kumar, Navin; Puljević, Cheneal; Heimer, Robert
Abstract: Introduction and Aims: Large for‐profit firms supply the majority of US state‐legal cannabis stores and some firms have attempted to shape cannabis‐related policies. Understanding firms' motivations for participation in the cannabis space is critical, given firms' possible links to cannabis usage patterns. Key decision‐makers (KDM) in the cannabis space may have information unavailable to lower ranking staff, and may influence firm decision‐making and consequently US cannabis usage practises. We present the findings of a qualitative study investigating the views of KDMs in the cannabis market, on large cannabis firms' motivations for participation in the space. Design and Methods: Data were collected through 37 semi‐structured interviews with a convenience sample of KDMs in the US cannabis space, representing both for‐profit and non‐profit organisations. Thematic analysis, with an inductive approach, was used to analyse the data. Results: KDMs reported three non‐exclusive motivations for large cannabis firms' participation in the space; to seek profit, to mitigate social inequity and to provide cannabis as medicine. Within the theme relating to profit, findings suggest that for‐profit and non‐profit organisations in the space may be cognisant of the other's goals, representing a symbiotic relationship. Discussion and Conclusions: We suggest that firms may have reasons to enter the space not necessarily centred on increasing use. Although non‐profits and for‐profits have different agendas, the bottom line for both groups is to expand access. Policy‐makers should be aware of that fact, and set policies which consider the two groups as a unified whole.